Murine Endometrial Organoids to Model Chlamydia Infection - Bishop, R. Clayton; Boretto, Matteo; Rutkowski, Melanie R.; Vankelecom, Hugo; Derré, Isabelle (Frontiers in Cellular and Infection Microbiology, 2020)
The obligate intracellular bacterium Chlamydia trachomatis is the leading cause of bacterial sexually transmitted infections. Once internalized in host cells, C. trachomatis undergoes a biphasic developmental cycle within a membrane-bound compartment, known as the inclusion. Successful establishment of the intracellular niche relies on bacterial Type III effector proteins, such as Inc proteins. In vitro and in vivo systems have contributed to elucidating the intracellular lifestyle of C. trachomatis, but additional models combining the archetypal environment of infection with the advantages of in vitro systems are needed. Organoids are three-dimensional structures that recapitulate the microanatomy of an organ's epithelial layer, bridging the gap between in vitro and in vivo systems. Organoids are emerging as relevant model systems to study interactions between bacterial pathogens and their hosts. Here, we took advantage of recently developed murine endometrial organoids (EMOs) and present a C. trachomatis-murine EMO infection model system. Confocal microscopy of EMOs infected with fluorescent protein-expressing bacteria revealed that inclusions are formed within the cytosol of epithelial cells. Moreover, infection with a C. trachomatis strain that allows for the tracking of RB to EB transition indicated that the bacteria undergo a full developmental cycle, which was confirmed by harvesting infectious bacteria from infected EMOs. Finally, the inducible gene expression and cellular localization of a Chlamydia Inc protein within infected EMOs further demonstrated that this model is compatible with the study of Type III secreted effectors. Altogether, we describe a novel and relevant system for the study of Chlamydia-host interactions.